Outlines of the cultural surveys of the Book of Aukštaitija - Petreikis, Tomas (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] The region of Aukštaitija, retaining its place within certain cultural and economic borders, intrinsically provides conditions for the development of book phenomena, the entirety of which is called regional book culture. Its recognition is important from perspectives both theoretical and practical, especially while designing and conducting more directed regional surveys. The course of said surveys is concentrated on the definition of the region’s space as well as on the application of approaches of complex and systemic surveys. Complex surveys allow to comprehend the origins of separate phenomena, their content, development and prevalence. Systemic surveys cover the mutual relations of the elements of book culture; phenomena are studied not separately but as a system of relations. There currently is a lack of complex surveys regarding a more detailed, systemic analysis of book culture phenomena. A unique phenomenon of book culture native to the Aukštaitija region is dialectal literature published in the East Highland subdialect. Published material is singled out on a lingual basis; because of the specificity of the addressee, the analysis is integral and conducted by evaluating the integer of the book of Aukštaitija. Any faster surveys are delayed because of the inteferences from the Lithuanian administrative reform; more directed initiatives are also lacking.